“Authenticating” the Role of Authentic Leadership: Examining its Relationship with Trust in the Leader, Psychological Sense of Community and Engagement in the Virtual & Hybrid Workplace - Mamaregane, Thato (Organisational Psychology, 2024)
The coronavirus pandemic (COVID-19) has changed the trajectory of the working world. As the world learnt to socially distance, the working world shifted to a virtual setting. Individuals who had to perform this shift had to adjust without preparation. Individuals leading teams, for example, often knew how to do so in face-to-face interactions while in physical proximity to others but might not have known what successful leadership would require in virtual or, later, hybrid (partly virtual, partly physical) workspaces. This dissertation considered one leadership style, authentic leadership, and its relationship with employees' work engagement through their trust in their leader because past research found relationships between these variables in a physical working environment. Therefore, this dissertation aimed to understand whether these results still stand in a virtual and hybrid work environment. Research with individuals working in office settings has shown that these variables are related. It tests the assumption that the same relationships apply in the virtual workspace but that, here, an additional variable is of importance. In the virtual space, a psychological sense of community is required for authentic leadership to create engagement via trust in the leader. To test the assumption, a descriptive, quantitative study was conducted. N = 160 employees who worked virtually or in a hybrid setting worldwide completed a survey including established scales to measure the four psychological constructs of interest. Employees who perceived their leader as authentic had greater cognitive and affective trust in their leader, but neither cognitive nor affective trust predicted work engagement. The expected mediation effect was thus not found. A psychological sense of community was found to moderate the relationship between perceived authentic leadership and one aspect of work engagement (absorption|dedication) but not the vigour aspect of work engagement. The results highlight that the relationships between work related attitudes and behaviour might differ in virtual workspaces than when working face to face. The exploration of the four hypotheses determined that the research questions were not supported. However, this research is relevant as it explored employees' insights into hybrid or virtual workplaces, as many more organisations have migrated their working environments to these spaces.